2020
DOI: 10.3390/brainsci10010055
|View full text |Cite
|
Sign up to set email alerts
|

Motor Program Transformation of Throwing Dart from the Third-Person Perspective

Abstract: The perspective of perceiving one’s action affects its speed and accuracy. In the present study, we investigated the change in accuracy and kinematics when subjects throw darts from the first-person perspective and the third-person perspective with varying angles of view. To model the third-person perspective, subjects were looking at themselves as well as the scene through the virtual reality head-mounted display (VR HMD). The scene was supplied by a video feed from the camera located to the up and 0, 20 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(122 reference statements)
0
6
0
Order By: Relevance
“…It was argued that local pain may result in more attention to the part of the body (i.e., internal attention) underlying learning ( Dancey et al, 2016b ), which in turn can lead to more changes in cortical neuroplasticity ( Rosenkranz and Rothwell, 2004 ), and subsequently improve in the learning of motor tasks. However, a recent study ( Tumialis et al, 2020 ) indicated that external attention can engender more accuracy and better performance in comparison to internal attention, including performing a task in the presence of pain. Whereas Mavromatis et al (2017) applied a similar experimental pain model compared to the work of Dancey et al (2014 , 2016a , b , 2018) , they did not observe any significant effect of acute pain on the skill learning acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…It was argued that local pain may result in more attention to the part of the body (i.e., internal attention) underlying learning ( Dancey et al, 2016b ), which in turn can lead to more changes in cortical neuroplasticity ( Rosenkranz and Rothwell, 2004 ), and subsequently improve in the learning of motor tasks. However, a recent study ( Tumialis et al, 2020 ) indicated that external attention can engender more accuracy and better performance in comparison to internal attention, including performing a task in the presence of pain. Whereas Mavromatis et al (2017) applied a similar experimental pain model compared to the work of Dancey et al (2014 , 2016a , b , 2018) , they did not observe any significant effect of acute pain on the skill learning acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…The role of AI mainly functions for data classification, monitoring, and visualization among the included studies. Furthermore, 80% (43/54) of the studies recruited participants for user study [ 75 , 76 , 78 - 81 , 83 - 88 , 90 , 92 , 93 , 95 - 105 , 107 - 110 , 113 - 116 , 118 - 124 , 127 , 128 ]. Twelve articles used public data set [ 78 , 82 , 89 , 91 , 94 , 106 , 111 , 112 , 117 , 125 - 127 ].…”
Section: Resultsmentioning
confidence: 99%
“…The studies that involved placing sensors on the full body and in environments were widely reported [ 84 , 94 , 96 , 103 , 109 - 112 , 115 , 116 , 119 , 122 , 123 ], and the purposes of using full-body motion tracking are commonly argued for analyzing specific movements or securing the credibility of system evaluations [ 94 , 106 , 110 , 112 , 115 , 116 , 123 ]. The investigations involving the placement of sensors in physical spaces mostly use motion capture and image processing techniques [ 117 , 119 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was argued that local pain may result in more attention to the part of the body underlying learning (Dancey et al, 2016b), which in turn can lead to more changes in cortical neuroplasticity (Rosenkranz & Rothwell, 2004), and subsequently improve in the learning of motor tasks. A recent study (Tumialis et al, 2020) indicated that external attention can engender more accuracy and better performance in comparison to internal attention, including performing a task in the presence of pain. Whereas Mavromatis and colleagues (Mavromatis et al, 2017) applied a similar experimental pain model compared to the work of Dancey (Dancey et al, 2016a; Dancey et al, 2014; Dancey et al, 2016b; Dancey et al, 2018), they did not observe any significant effect of acute pain on the skill learning acquisition.…”
Section: Discussionmentioning
confidence: 99%